PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI “INI KHAS DAERAHKU” UNTUK MENINGKATKAN HASIL DAN MINAT BELAJAR IPAS KELAS IV SD - Galuh Nawang Wulan; Tri Astuti (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The acceleration of digital technology in the education sector has significantly enhanced the integration of interactive learning media; however, elementary schools are still dominated by conventional media, and previous research has not extensively examined both student interest and learning outcomes simultaneously in the context of augmented reality. Therefore, this study is important to address this gap. This research focuses on the development of augmented reality learning media through the Assemblr Edu platform, which has met the criteria for validity and effectiveness in optimizing student learning outcomes and motivation in the IPAS subject “Ini Khas Daerahku” for fourth-grade students at SDN 1 Jati. The development of learning media in this study adopts a Research and Development (R&D) approach by implementing the 4D stages, which include definition, design, development, and dissemination. Data collection was conducted using pretest-posttest instruments, questionnaires, interviews, observations, and documentation, with data analysis techniques including normality tests, t-tests, and n-gain. Based on the validation test results, the media was deemed highly suitable for use after receiving a 87.5% rating from subject matter experts and 96% from media experts, with an overall average of 91.75%. Findings from the effectiveness test indicated that a significant improvement in performance occurred, with a pretest average score of 46.50 and a posttest average score of 86.75, as well as an N-gain of 0.76, which falls into the high category. This data indicates that the use of assemblr.edu-based augmented reality media is not only valid and effective in improving students' understanding of the material "This is Typical of My Region," but can also create interactive, engaging, and realistically relevant learning dynamics. ABSTRAK Akselerasi teknologi digital di sektor pendidikan secara signifikan mampu meningkatkan integrasi media pembelajaran berbasis interaktif, namun di sekolah dasar masih didominasi media konvensional dan penelitian sebelumnya belum banyak mengkaji secara simultan minat dan hasil belajar dalam konteks augmented reality, sehingga penelitian ini penting dilakukan untuk mengisi kesenjangan tersebut. Riset ini difokuskan pada pengembangan media pembelajaran augmented reality melalui platform assemblr edu yang telah memenuhi kriteria validitas serta efektivitas dalam mengoptimalkan hasil dan motivasi belajar peserta didik pada IPAS materi “Ini Khas Daerahku” kelas IV SDN 1 Jati. Pengembangan media pembelajaran dalam riset ini mengadopsi pendekatan Research and Developement (R&D) dengan mengimplementasikan tahapan 4D yang meliputi pendefinisian, perancangan, pengembangan, serta penyebaran. Pengumpulan data dilakukan melalui instrumen pretest-posttest, angket, wawancara, observasi, dan dokumentasi, dengan teknik analisis data mencakup uji normalitas, t-test, dan n-gain. Berdasarkan hasil uji validasi, media dinyatakan sangat layak pakai setelah memperoleh persentase 87,5 persen dari ahli materi dan 96 persen dari ahli media, dengan rerata total 91,75 persen. Temuan pada uji efektivitas mengindikasikan bahwa peningkatan performa terjadi secara signifikan dari nilai rerata pretest 46,50 dan posttest 86,75 serta N-gain 0,76 yang termasuk kategori tinggi. Data ini mengindikasikan bahwa pemanfaatan media augmented reality berbasis assemblr edu tidak hanya valid dan efektif untuk meningkatkan retensi pemahaman peserta didik terkait materi “Ini Khas Daerahku”, tetapi dapat menciptakan dinamika pembelajaran yang interaktif, menarik, dan relevan dengan realistis.